2018
DOI: 10.3390/su10030673
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Competing Models for Understanding Industrial Organization’s Acceptance of Cloud Services

Abstract: Cloud computing is the next generation in computing, and the next natural step in the evolution of on-demand information technology services and products. However, only a few studies have addressed the adoption of cloud computing from an organizational perspective, which have not proven whether the research model is the best-fitting model. The purpose of this paper is to construct research competing models (RCMs) and determine the best-fitting model for understanding industrial organization's acceptance of clo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 65 publications
0
10
0
Order By: Relevance
“…Low et al [29] identified technological, organizational, and environmental contexts with factors which were proposed in prior studies to understand decision components of cloud adoption. Chen et al [30] researched best-fitting models for adopting cloud services in an organization. Walther et al [31] developed a measurement index for accessing cloud system success with system quality, information quality, and net benefits.…”
Section: Cloud Computing Adoption and Influence Factorsmentioning
confidence: 99%
“…Low et al [29] identified technological, organizational, and environmental contexts with factors which were proposed in prior studies to understand decision components of cloud adoption. Chen et al [30] researched best-fitting models for adopting cloud services in an organization. Walther et al [31] developed a measurement index for accessing cloud system success with system quality, information quality, and net benefits.…”
Section: Cloud Computing Adoption and Influence Factorsmentioning
confidence: 99%
“…Thus, combining TOE variables strengthen the DOI theory has been accepted as a valuable idea [5]. The internal and external organisational characteristics of DOI have similar measurements like those of TOE's organisation context [7]. Despite the similarities, there are some key differences between the TOE and DOI.…”
Section: Related Workmentioning
confidence: 99%
“…A framework that would be beneficial in facilitating the understanding of digital transformation and innovation success is the technology-organization-environment (TOE), which classifies three areas that affect the process by which organizations implement or adopt technology. TOE has advanced to become a valuable theoretical lens for understanding new technology adoption for applicability in an organization [39] and a widespread theoretical perspective related to performance and innovation [40][41][42]. It is worth noting that the TOE framework does not identify specific factors, as these should be determined according to the research setting and research questions.…”
Section: Literature Review and Theoretical Frameworkmentioning
confidence: 99%
“…The TOE theoretical framework, on the other hand, is introduced into the research of enterprise digital innovation, which not only enriches the perspective of digital innovation research, but also broadens the application scope of the TOE model, that is to say, it breaks through the traditional application scenario analysis framework based on adopting innovative technologies. This is a response to existing research calling for practice in the areas of government policy, business model innovation, performance, and digital transformation [40][41][42], further exploring the specific connotation of the TOE framework in the Chinese context.…”
Section: Theoretical Implicationsmentioning
confidence: 99%